Communication Analysis of Men and Women in Ngayah Activity at Village Temple of Panji Village - Suandari, Made Suci (Lingua Scientia, 2012)
The purpose of this study was to find out the conversational style of four different castes of both men and women during the ngayah activity in Village temple. The design of this study is qualitative since the researchers concerned with the reasons related to the data not based on the percentage of the data analysis. There were six participants observed in this study, there were four men and two women. One participant was from Agung clan, one participant was from Dewa clan, two participants were from Gusti clan and two participants were from Jaba clan. The women were from Jaba status (clan). The observation was done in January, 2012. The data were gained from the observation. The researcher observed the participants and recorded their conversations. Then, the recorded data were transcribed into written form in order to make the analysis of the data easier. There was different language choice among the conversation of men and women in ngayah activity in Panji Village. The reasons of changing the language were influenced by some factors, like setting, status, and emotion (feeling).